2010
DOI: 10.1007/s11746-010-1657-z
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Sliding Wear Behaviour and Mechanical Properties of Jatropha Oil Cake‐Filled Glass‐Epoxy Composites

Abstract: The effect of Jatropha oil cake (JOC) filler incorporation into glass fabric-epoxy (G-E) composites and its sliding wear and mechanical properties were evaluated. The sliding distance and applied load are the process parameters at constant sliding velocity. The results show that JOC-filled composites exhibit better sliding wear performance at all test conditions. The wear loss increases with an increase in sliding distance and applied load, whereas under the same conditions, the specific wear rate decreases. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…Recently, relatively new polymerization methods such as acyclic diene metathesis polymerization [147] and ring-opening metathesis polymerization [148,149] of functionalized fatty alcohols have been employed to synthesize vegetable oil-based polymers as well. Polymerization of vegetable oils/derivatives in the presence of different organic or inorganic nanofillers produces polymer nano-composites, which are extensively applied in the automotive industry, especially as an antiwear coating/additive in lubricants [150].…”
Section: Conversion Of the Olefinic Functional Groups Into Cyclic Carmentioning
confidence: 99%
“…Recently, relatively new polymerization methods such as acyclic diene metathesis polymerization [147] and ring-opening metathesis polymerization [148,149] of functionalized fatty alcohols have been employed to synthesize vegetable oil-based polymers as well. Polymerization of vegetable oils/derivatives in the presence of different organic or inorganic nanofillers produces polymer nano-composites, which are extensively applied in the automotive industry, especially as an antiwear coating/additive in lubricants [150].…”
Section: Conversion Of the Olefinic Functional Groups Into Cyclic Carmentioning
confidence: 99%
“…Hence, their product, the (r e) factor, may become smaller in the case of a particulate filled composite compared to the neat matrix. Mohan et al [7] found that Jatropha oil cake filled glass/epoxy composite had the lowest specific wear rate, which had the lowest (r e) factor. They concluded that the incorporation of Jatropha oil cake to glass/epoxy composite, increased both e and r. This observation was attributed to the elastomeric nature of Jatropha oil cake, which had good bonding with the epoxy matrix.…”
Section: Specific Wear Ratementioning
confidence: 99%
“…Basavarajappa et al [5,6] showed that incorporation of silicon carbide and graphite to glass/epoxy composites reduced their wear. Mohan et al [7] incorporated jatropha oil cake to glass/epoxy composites to enhance their wear resistance by reducing their coefficient of friction. Suresha et al [8] found that wear resistance of glass/epoxy composites was enhanced by Cenospheres obtained from fly ash.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present work wear studies have been carried out for graphitefilled glass reinforced-epoxy composite and unfilled glassreinforced-epoxy composites at various temperatures such as 30 C, 50 C, 70 C and 90 C and reported. Considerable information=data related to this present work is available in the literature [12][13][14][15][16][17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%